The SARS-CoV-2 Pandemic Impacts the Management of Swiss Pediatric Intensive Care Units - Soomann, Maarja; Wendel-Garcia, Pedro D.; Kaufmann, Mark; Grazioli, Serge; Perez, Marie-Helene; Hilty, Matthias P.; André, Maya C.; Brotschi, Barbara (Frontiers in Pediatrics, 2022)
The impact of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic on pediatric intensive care units (PICUs) is difficult to quantify. We conducted an observational study in all eight Swiss PICUs between 02-24-2020 and 06-15-2020 to characterize the logistical and medical aspects of the pandemic and their impact on the management of the Swiss PICUs. Nine patients admitted to Swiss PICUs during the study period suffer pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS), constituted 14% (9/63) of all SARS-CoV-2 positive hospitalized patients in Swiss children´s hospitals and caused a higher workload (total Nine Equivalents of nursing Manpower use Score (NEMS) points, p = 0.0008) and were classified to higher workload categories (p < 0.0001) than regular PICU patients (n = 4881) admitted in 2019. The comparison of the characteristics of the 8 Swiss PICUs shows that they were confronted by different organizational issues arising from temporary regulations put in place by the federal council. These general regulations had different consequences for the 8 individual PICUs due to their different characteristics. Additionally, the temporal relationship of these different regulations has influence on the available PICU ressources, dependent on the characteristics of the individual PICU. As pandemic continues, reflecting and learning from experience is essential to reduce the workload, optimize the occupancy and dispose the ressources in each individual PICU. In a small country as Switzerland, PICUs should be organized dependent of the local health care policy and not nationwide due to their individual characteristics.